1998
DOI: 10.1037/0278-6133.17.6.551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social support and personal coping resources on depressive symptoms: Different for various chronic diseases?

Abstract: Effects of psychosocial coping resources on depressive symptoms were examined and compared in older persons with no chronic disease or with recently symptomatic diabetes mellitus. lung disease, cardiac disease, arthritis, or cancer. The 719 persons without diseases reported less depressive symptoms than the chronically ill. Direct favorable effects on depressive symptoms were found for having a partner, having many close relationships, greater feelings of mastery, greater self-efficacy expectations, and high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
139
3
9

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(162 citation statements)
references
References 31 publications
11
139
3
9
Order By: Relevance
“…In an investigation of depression in adults over the age of 50, Dean et al (1990) found that expressive support from one's spouse and friends reduced depression. Penninx et al (1998) provided evidence for a favourable effect of social support on depressive symptoms in the sense that having a partner and having many close relationships was associated with fewer depressive symptoms. In particular, spouses were found to be most important for psychological well-being (Dean et al 1990).…”
Section: Determinants Of Mental Healthmentioning
confidence: 98%
“…In an investigation of depression in adults over the age of 50, Dean et al (1990) found that expressive support from one's spouse and friends reduced depression. Penninx et al (1998) provided evidence for a favourable effect of social support on depressive symptoms in the sense that having a partner and having many close relationships was associated with fewer depressive symptoms. In particular, spouses were found to be most important for psychological well-being (Dean et al 1990).…”
Section: Determinants Of Mental Healthmentioning
confidence: 98%
“…Of the 42 total studies, 3 (7%) did not provide enough information to be included in the OR or point prevalence calculations. Two of these three studies (32,33) reported only the statistical comparison of the mean depression scale scores of diabetic versus nondiabetic subjects, and the other (34) reported only lifetime rates of depression.…”
Section: Methodsmentioning
confidence: 99%
“…Because depressive symptoms increase risk of death in older adults (Blazer et al 2001), lead to increased caregiver depression (Neundorfer et al 2001), and increase the risk of AD in cognitively impaired individuals (Alexopoulos et al 1993;Modrego and Ferrandez 2004), it is important to detect possible factors contributing to depression in old age. Research has shown a differential impact of social support and personal coping resources on depression in individuals with various chronic diseases (Bisschop et al 2004;Penninx et al 1998); however, the protective impact of social support and motivational processes on depression in old age might even increase in individuals with the increasing cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%